In the Eyes of the Beholder: Experimental Evidence on the Contested Nature of Materiality in Sustainability Reporting. (December 2020) - Reimsbach, Daniel; Schiemann, Frank; Hahn, Rüdiger; Schmiedchen, Eric
Materiality is an ambiguous concept in sustainability reporting where potential users are more heterogeneous than in financial reporting. Building on decision usefulness and dual process theory, we scrutinize in an experimental setting how two important stakeholder groups react to manipulations of the topic of nonfinancial information while controlling for differences in nonfinancial performance. We find that potential employees consider nonfinancial information as generally more material compared with capital market participants. Furthermore, for capital market participants, the nonfinancial topic of energy is more material than the topic of biodiversity, while for potential employees, both topics are equally material. Capital market participants seem to follow a more analytic decision-making process than potential employees. Capital market participants also adjust their decisions in combination with quantitative performance differences, and their risk assessment of a company mediates their decisions. Our findings show that materiality of nonfinancial information lies in the eye of the beholder.